A post‐HF study on the halogen bonding interaction of pyrene with diatomic halogen molecules. Issue 9 (2nd February 2016) - Sütay, Berkay; Yurtsever, Mine; Yurtsever, Ersin
Abstract : We present a detailed SCS‐MP2 study on the potential energy curves (PEC) for interactions between diatomic halogen molecules and pyrene. BSSE corrected CCSD[T] energies at equilibrium distances are computed and compared to CCSD(T) energies. The most stable conformation of these weakly bound van der Waals complexes is almost linear in the perpendicular direction to the pyrene plane. The complexes of highly polarizable bromine and iodine molecules with pyrene are very stable and they carry rather large number of vibrational states. Despite its small size, F2 also forms strong halogen bonding similar to Br2 and I2 . The interaction between Cl2 and pyrene is the weakest and it is attributed to the highest polarizability/ molar mass ratio of chlorine among the others. I2 ‐pyrene is found to be the most stable complex due to the strongest mutual polarization effects and is carrying more than 60 vibrational states. Due to the rather large number of electrons in some complexes, the relativistic corrections are also considered. © 2016 Wiley Periodicals, Inc. Abstract : Pyrene is chosen as a model for graphene‐like surfaces to allow the rigorous theoretical treatment of its interaction with halogen molecules. SCS‐MP2 calculations, including relativistic corrections, offer insight on the nature of the halogen bonding, polarization effects, vibrational bound states, and molecular orbitals in these weakly bound van der Waals complexes.